Determinants of Transfer Pricing Decisions and Its Impact on Tax Avoidance - Alexander, Nico (Riset Akuntansi dan Keuangan Indonesia, 2024)
The purpose of this study was to obtain empirical evidence regarding the variables that may affect a company's decision of employing transfer pricing along with how that choice may affect tax avoidance. The variables that are used consist of the bonus mechanism, debt convenant, and tunneling incentive. The study used a two-stage regression analysis to analyze its hypotheses. 12 multinational manufacturing corporations listed between 2019 and 2021 on the Indonesia Stock Exchange represent the research sample. The purposive technique was the method used for selecting the research sample. The findings proved that the tunneling incentive has a negative impact on the decision of transfer pricing. This indicates the decision to utilize transfer pricing will be fewer depending on the percentage of foreign ownership in the business. In meanwhile, transfer pricing decisions are unaffected by bonus mechanism and debt covenants. Additionally, the findings demonstrate that tax evasion is unaffected by transfer pricing. This outcome demonstrates that there are still alternative strategies for avoiding taxes; transfer pricing has not become a significant one. The results of this study cannot be applied to other sectors within the company because it solely examines multinational manufacturing companies. Future research can use different variables or different measurements to get better results because not all of the variables used have an impact on transfer pricing or tax avoidance. The study's findings may be useful as a framework for other researchers looking into related subjects, and the results can also provide parties responsible for Indonesian taxation with more information to help them develop regulations related to transfer pricing and tax avoidance.